2007
DOI: 10.1111/j.1708-8240.2007.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of In Vitro Methods Used to Promote Adhesive Interface Degradation: A Critical Review

Abstract: The in vitro methods used to simulate bond degradation may describe important points related to the clinical performance of restorations. This article evaluates the mechanism of the in vivo biodegradation of adhesive interfaces as well as the influences that various testing methods have on these bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
159
0
24

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(186 citation statements)
references
References 92 publications
(218 reference statements)
3
159
0
24
Order By: Relevance
“…While some authors found no significant effect on adhesion [31,32], others did [33,34]. Its effect on bond strength is contradictory and seems to depend on the number of cycles [35,36], size of the specimens [36,37] and the C-factor [38,39]. Thus, the clinical relevancy of such aging methods has to be correlated with clinical studies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…While some authors found no significant effect on adhesion [31,32], others did [33,34]. Its effect on bond strength is contradictory and seems to depend on the number of cycles [35,36], size of the specimens [36,37] and the C-factor [38,39]. Thus, the clinical relevancy of such aging methods has to be correlated with clinical studies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The laser beam was applied using a noncontact method, focused at a distance of 12 mm from the substrate with water spray of 1.5 mL/min (9).…”
Section: Specimen Preparationmentioning
confidence: 99%
“…The degradation of the bonding interface has a considerable influence on the clinical performance and survival of the resin composite restorations (9,10). Studies have shown that matrix metalloproteinase (MMP) inhibitors, such as chlorhexidine (CHX) and more recently sodium fluoride (NaF), are able to preserve the structural integrity of the hybrid layer and consequently improve the longevity of restorations (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of bond degradation seems be complex including the size of the adhesive area where water is indispensable for this action [12]. The water sorption decreases the frictional forces between the polymer chains of the bonding area that eventually decreases the mechanical properties of the resin [12].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, thermocycling is used in some studies [7,9] aiming to induce contraction/expansion stresses at the interface that results from the thermal expansion coefficient of the materials [12]. This can induce crack propagation along the interface and consequently debond the materials.…”
Section: Introductionmentioning
confidence: 99%